Ceramic nuclear fuel fracture modeling with the extended finite element method. (January 2020) - Jiang, Wen; Spencer, Benjamin W.; Dolbow, John E.
Highlights: Application of the extended finite element method (X-FEM) to model thermally driven fracture in ceramic nuclear fuel with fractures represented in a discrete, mesh-independent manner. Detailed description of the implementation of X-FEM in the open-source MOOSE framework and the Bison fuel performance code. Demonstration of this algorithm on thermo-mechanical benchmark problems, on stationary cracks in nuclear fuel, and on propagating cracks in nuclear fuel. Abstract: Ceramic fuel pellets used in nuclear light water reactors experience significant fracture due to the high thermal gradients experienced under normal operating conditions. This has important effects on the performance of the fuel system. Because of this, a realistic, physically based fracture modeling capability is essential to predict fuel behavior in a wide variety of normal and off-normal conditions. The extended finite element method (X-FEM) is a powerful method to represent arbitrary propagating discrete cracks in finite element models, and has many characteristics that make it attractive for nuclear fuel performance analysis. This paper describes the implementation of X-FEM in a multiphysics fuel performance code and presents applications of that capability. These applications include several thermal mechanics fracture benchmark problems, which demonstrate the accuracy of this approach. It also includes application of this capability to study nuclear fuel fracture, both on stationary and propagating cracks. The study on stationary cracks shows the effects of interactions between cracks, and aids in understanding the process of crack propagation during a power ramp. The propagating crack case demonstrates random initiation and subsequent propagation of interacting thermally induced cracks during an initial ramp to full power with fresh fuel.